Structuration theory investigation of elite Rugby players` perceptions on how the transition from player to retired player impacted their significant others (International Review for the Sociology of Sport, 2025)
This study investigated how male Australian National Rugby League (NRL) players believed their transition to retirement from professional sport impacted their significant other(s), particularly their partner. We used a constructivist paradigm to frame structuration theory to interpret findings from interpretative analysis of qualitative data obtained from semi-structured interviews with 21 retired players. Themes arrived at interpretatively from the data and identified as perceived impacts were changes in the time spent with family, altered lifestyle status, and the need for family relationship support. In supporting elite players through the preparation and transition to retirement it was found that participants believed that it is not only the players that need support in the transitioning to retirement process but also those who support them, especially their significant others.